PENGARUH DIGITAL BANKING DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON ASSETS (ROA) PADA PT BANK CENTRAL ASIA TBK PERIODE 2015–2024 - Clarrissa Litania Iskandar; Ari Bramasto; Taufik Sadikin (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2026)
This study aims to analyze the effect of Digital Banking and Debt to Equity Ratio (DER) on Return on Assets (ROA) at PT Bank Central Asia Tbk during the period 2015–2024. Digital Banking is measured using a dummy variable, while DER represents the company's capital structure and ROA serves as an indicator of profitability. This study employed a quantitative approach using secondary data obtained from the quarterly financial statements of PT Bank Central Asia Tbk from 2015 to 2024, resulting in 40 observations. Data were analyzed using multiple linear regression with the Cochrane–Orcutt method and processed using IBM SPSS Statistics 25. The results indicate that Digital Banking does not have a significant effect on ROA (t = -0.412; p = 0.683), and DER also does not have a significant effect on ROA (t = -1.539; p = 0.133). Furthermore, Digital Banking and DER simultaneously do not have a significant effect on ROA. These findings suggest that the profitability of PT Bank Central Asia Tbk is influenced more by other factors beyond Digital Banking and capital structure, such as operational efficiency, asset quality, economic conditions, and managerial policies. Therefore, Digital Banking and DER cannot be considered dominant determinants of the company's profitability during the study period.